Description du verbe "donner" et son homologu - Bakhouche Afef (My University, 2022)
Absrait : Transformational grammar is a grammar with rewriting and substitution rules that establish equivalences between various types of sentences, which it accounts for by explicit operations. On the one hand, transformation is considered an experimental tool for discovering new facts on language, and to discover mechanisms, elements and data that are not directly shown to the observer. From a point of view; we can consider transformational grammar as a description of traditional grammar. In our research on Zellig Harris' transformational grammar theory; we have described the verb "to give" and its counterpart the verb "أعطى" a3taa; by specifying the description of their distributional and transformational properties; where we adopted as a corpus of study different examples of literary works of the 18th / 19th centuries in French, then we transformed them into classical Arabic; where most examples did not contain the verb "أعطى" a3taa; so we made some changes while keeping the same meaning. At the same time we made a comparative study between the latter two; through the different equivalents taken by each of the two verbs. تلخيص: